NK- and T-cell granzyme B and K expression correlates with age, CMV infection and influenza vaccine-induced antibody titres in older adults - Verschoor, Chris P.; Picard, Emilie; Andrew, Melissa K.; Haynes, Laura; Loeb, Mark; Pawelec, Graham; Kuchel, George A. (Frontiers in Aging, 2023)
Granzymes are a family of serine-proteases that act as critical mediators in the cytolytic and immunomodulatory activities of immune cells such as CD8+ T-cells and natural killer (NK) cells. Previous work indicates that both granzyme B (GZB) and K (GZK) are increased with age in CD8+ T-cells, and in the case of GZB, contribute to dysfunctional immune processes observed in older adults. Here, we sought to determine how GZB and GZK expression in NK-cells, and CD4+, CD8+, and gamma-delta T-cells, quantified in terms of positive cell frequency and mean fluorescence intensity (MFI), differed with age, age-related health-traits and the antibody response to high-dose influenza vaccine. We found that the frequency and MFI of GZB-expressing NK-cells, and CD8+ and Vδ1+ T-cells, and GZK-expressing CD8+ T-cells was significantly higher in older (66-97 years old; n=75) vs. younger (24-37 years old; n=10) adults by up to 5-fold. There were no significant associations of GZB/GZK expression with sex, frailty or plasma levels of TNF or IL-6 in older adults, but those who were seropositive for cytomegalovirus (CMV) exhibited significantly higher frequencies of GZB+ NK-cells, and CD4+, CD8+ and Vδ1+ T-cells, and GZK+ CD8+ T-cells (Cohen’s d= 0.5 to 1.5). Pre-vaccination frequencies of GZB+ NK-cells were positively correlated with vaccine antibody responses against A/H3N2 (d= 0.17), while the frequencies of GZK+ NK and CD8+ T-cells were inversely associated with A/H1N1 (d= -0.18 to -0.20). Interestingly, GZK+ NK-cell frequency was inversely correlated with pre-vaccination A/H1N1 antibody titres, as well as those measured over the previous four years, further supporting a role for this subset in influencing vaccine antibody-responses. These findings further our understanding of how granzyme expression in different lymphoid cell-types may change with age, while suggesting that they influence vaccine responsiveness in older adults.